DIGITAL TRANSFORMATION OF BANK ASSET MANAGEMENT: LESSONS FROM THE EU DIGITAL FINANCE STRATEGY FOR UZBEKISTAN (JEAN MONNET MODULE) (Marketing Journal, 2025)
The acceleration of digital transformation across the European Union has reshaped traditional models of bank asset management and the broader landscape of financial intermediation. The EU Digital Finance Strategy (2020 –2024) establishes a unified framework that promotes innovation, competition, and financial stability within an integrated digital single market. This paper explores how the guiding principles and institutional mechanisms of the EU strategy can inform the modernization of bank asset management in Uzbekistan. Drawing on comparative policy analysis and conceptual interpretation, the study identifies opportunities to enhance asset transparency, efficiency, and sustainability through the adoption of European approaches. The research highlights that aligning Uzbekistan’s financial modernization agenda with EU best practices —such as open finance systems, standardized digital identification, and regulatory innovation —can strengthen the country’s financial resilience and improve long-term competitivenes s of its banking sector.
Keywords: digital finance; EU Digital Finance Strategy; bank asset management; open finance; Uzbekistan; financial innovation; regulatory frameworks